Nucleótidos libres en la levadura y adaptación a la utilización de galactosa - Palleroni, Norberto J. (1962)
In previous experiments performed in this laboratory, we have observed that cells grown far 5 hours in autolyzed yeast with 2 per cent glucose, utilize galactose after an adaptation period which is considerably longer than the one for cells grown for 24 hours in the same medium. This phenomenon can be correlated with the composition of the nucleotide pool of the respective cells. Thus, 5 hours-old cells have much less quantities of uridine compounds, particularly of UDPG. The delay in adapting to galactose utilization could thus be attributed to this deficiency in young cells, although it is also possible that the uridine compunds are converted to peptidyl-nucleotides which could function as repressors in the induced synthesis of the enzymes involved in galactose metabolism.